2017
DOI: 10.1016/j.arthro.2017.08.116
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Arthroscopic Superior Capsule Reconstruction with Dermal Allograft

Abstract: Despite the growing interest on delaminated rotator cuff tear, the optimal surgical method is still controversial. In this prospective study, the result of two different surgical methods; en masse repair and separate double layer double row repair were compared. Both treatments were effective in improving clinical outcomes. Lower pain scores were seen in separate double-layer double-row repair. ABSTRACT DATA Introduction: Recently, there has been a growing interest on the delaminated tear of full thickness rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
204
2
10

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(225 citation statements)
references
References 0 publications
9
204
2
10
Order By: Relevance
“…Further, SCR may be a rational treatment option for relatively young patients with joint-conserving surgery and non-recoverable RCT. In contrast, it is a technically difficult procedure that requires extension of operation time and the risk of associated complications, such as infection, often increases; moreover, the materials needed and the effects of using SCR are not yet established [21]. Satisfactory results have been reported in SCR which surpasses other treatment outcomes and is becoming popular, and few studies have reported on the postoperative results and indications.…”
Section: Introductionmentioning
confidence: 99%
“…Further, SCR may be a rational treatment option for relatively young patients with joint-conserving surgery and non-recoverable RCT. In contrast, it is a technically difficult procedure that requires extension of operation time and the risk of associated complications, such as infection, often increases; moreover, the materials needed and the effects of using SCR are not yet established [21]. Satisfactory results have been reported in SCR which surpasses other treatment outcomes and is becoming popular, and few studies have reported on the postoperative results and indications.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Min 10 state in their clinical study that graft thickness, not the graft type, reduced superior translation. Denard et al 14 reported an overall success rate of 70%, but only 40% success when using a 1-mm graft. When choosing a graft, they report the advantages of a commercially available 3-mm dermal allograft and reductions in both operative time and autologous graft harvest morbidity.…”
Section: See Related Article On Page 1243mentioning
confidence: 99%
“…His ingenious solution was the SCR, which was a minimally invasive, joint-preserving option that the rest of the world would soon adopt as a legitimate alternative to the RSA and tendon transfers. [3][4][5][6][7][8] To further complicate the issue, stringent regulation and lack of tissue banks limit the availability of allograft tissue in Japan. To meet this challenge, Mihata used fascia lata autograft to reconstruct the superior capsule.…”
Section: See Related Article On Page 579mentioning
confidence: 99%